(untitled) (Current Problems in Rail Vehicles, 2021)
The contribution deals with the description of the electric unit type 16Ev from the production of ŠKODA TRANSPORTATION a.s. / ŠKODA VAGONKA a.s. The electric multiple unit will be put into operation on wide gauge lines in Latvia. The train will be operated by the Latvian Railways (Pasažieru vilciens).